2015
DOI: 10.1071/wf15011
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint from helitankers: sustainable decision making in aerial wildfire fighting

Abstract: Abstract. Carbon footprint (CF) can be a key factor stimulating innovation while driving sustainable decision making.The air transport sector and wildfires are considered to be relevant contributors to greenhouse gas emissions. Among the available resources for wildfire suppression, aerial firefighting -particularly using helitankers -is the most effective method. However the high economic costs and fuel-related emissions incurred by helitankers prevent their widespread use. This work aims to calculate the CF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Second, although studies on CF have often focused on Scope 1 and Scope 2 emissions, our findings also confirm the importance of Scope 3 emissions, as previously pointed out (Alvarez et al, ; Carballo‐Penela and Castromán‐Diz, ). Hence, organizations interested in reducing the CF of their products should consider actions aimed at reducing Scope 3 emissions when designing environmental strategies.…”
Section: Discussionsupporting
confidence: 91%
“…Second, although studies on CF have often focused on Scope 1 and Scope 2 emissions, our findings also confirm the importance of Scope 3 emissions, as previously pointed out (Alvarez et al, ; Carballo‐Penela and Castromán‐Diz, ). Hence, organizations interested in reducing the CF of their products should consider actions aimed at reducing Scope 3 emissions when designing environmental strategies.…”
Section: Discussionsupporting
confidence: 91%
“…The findings showed that these direct impacts related to combustion of fossil fuels and the impacts from purchased electricity presented less pressure to the environment than the indirect impacts generated by upstream and downstream activities in the supply chain. The importance of re-cognizing these indirect impacts has already been stated by authors, as they could be the main source of the environmental impacts [53,54]. Fig.…”
Section: The Environmental Footprint Of the Dam's End-of-life Phasementioning
confidence: 90%